La disciplina y su influencia en el aprendizaje de los estudiantes de octavo año de básica. - Ipiales, Jenifer S. (2022)
The research work that is presented has the purpose of determining how the discipline influences the learning of the students of Eighth Year of Parallel B and C of the School of Basic Education "July 9". Currently the discipline has been altered by social and personal factors that influence learning, becoming two issues that afflict teachers and society in general. The methodology proposed in this high-level academic article corresponds to a non-experimental design, with a descriptive and correlational type of research; For data collection, the survey technique was used, based on the Likert assessment scale, the instrument applied was the questionnaire made in Google Forms to 74 students, the data was processed in the statistical system SPSS version 20.0. Regarding the results, the collection instrument has a degree of reliability of 0.943 measured with Cronbach's Alpha, the reliability and factorial analysis is applied, while working with the descriptive and normality tests, where considers a confidence level of 95% and a margin of error of 5%, determining that it is a non-parametric statistic, for which the alternative hypothesis is accepted: As a conclusion, according to the Spearman correlation table, it is determined that there is a significant relationship between both variables of 54%, which is good.